Design and simulation of a Sierpinski Carpet Fractal PIFA for WLAN and HiperLAN application - Ismahayati, Adam (Institute of Electrical and Electronics Engineers (IEEE), 2011)
Link to publisher's homepage at http://www.ieee.org/